2005
DOI: 10.1038/nn1425
|View full text |Cite
|
Sign up to set email alerts
|

Optic ataxia errors depend on remapped, not viewed, target location

Abstract: Optic ataxia is a disorder associated with posterior parietal lobe lesions, in which visually guided reaching errors typically occur for peripheral targets. It has been assumed that these errors are related to a faulty sensorimotor transformation of inputs from the 'ataxic visual field'. However, we show here that the errors observed in the contralesional field in optic ataxia depend on a dynamic gaze-centered internal representation of reach space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 12 publications
10
74
0
Order By: Relevance
“…Likewise, establishing correlations between hand and eye motor commands would allow the specification of hand motor commands in gazecentered coordinates Engel et al, 2002;Crawford et al, 2004). In visually guided reaching, there is evidence that both targets and the hand are represented in gazecentered frames of reference in various brain regions (Mushiake et al, 1997;Batista et al, 1999;Stuphorn et al, 2000;Buneo et al, 2002;Medendorp et al, 2003;Khan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, establishing correlations between hand and eye motor commands would allow the specification of hand motor commands in gazecentered coordinates Engel et al, 2002;Crawford et al, 2004). In visually guided reaching, there is evidence that both targets and the hand are represented in gazecentered frames of reference in various brain regions (Mushiake et al, 1997;Batista et al, 1999;Stuphorn et al, 2000;Buneo et al, 2002;Medendorp et al, 2003;Khan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It was argued that a more appropriate characterization of optic ataxia should emphasize the distinction between central and peripheral vision rather than the distinction between perception and action 7 . Other studies have shown that optic ataxia affects only specific aspects of visuomotor behaviour 14 and egocentric coding 15 . It thus appears that neither the perception/action nor the allocentric/egocentric distinction can provide a satisfactory account of this complex disorder.…”
Section: An Allocentric Rather Than Perceptual Deficit In Patient Dfmentioning
confidence: 96%
“…Moreover, these patients presenting with OA without neglect, resulting from dorsal PPC lesions (i.e. lesions of the SPL and the IPS), have shown preserved visual remapping in the context of a trans-saccadic pointing task ( [45,46]; figure 4a). As a consequence, the dorsal PPC region, damaged in OA patients and involved in visuo-manual transformations, cannot be considered to be a region crucially involved in visual remapping.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the visual stimulus extinguishes and the subject is requested to produce a saccade that crosses the stimulus location and brings its location into the opposite visual space (across-hemifield visual remapping conditions). Behaviour [46] and brain activity [47][48][49] have demonstrated that, consequent to the saccade, the representation of the (extinguished) visual stimulus was transferred to the ipsilateral hemisphere. Neuroimaging studies have shown this interhemispheric transfer between homologous cortical regions, at the level of the posterior parietal cortices (PPC; [48,49]; figure 2a) or the occipital striate and extrastriate cortices [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation